Into the Broken Lands - Huff, Tanya (Daw Books, Inc., 2022)
The Heirs of Marsan, to save their people, must entrust their lives and the lives of everyone they protect, to someone who shouldn't exist, who cannot be controlled, and who will challenge everything they believe about themselves.